Physical and chemical properties of Nam Prig Noom, a Thai green-chili paste, following ultra-high pressure and thermal processes - Arunee Apichartsrangkoon (2018)
A study of processing green-chili pastes (Nam Prig Noom) by pressurization (100-600 MPa/30-50°C/20 min), pasteurization (90°C/3-5 min) or sterilization (121°C/4 min), subsequently, their physical, biochemical and microbiological qualities as well as the sensory acceptance were assessed. It was found that pressure at low levels (100-300 MPa) could improve activities of enzyme peroxidase (POD), polyphenoloxidase (PPO) and lypoxygenase (LOX) in the chili paste by more than 100%, while pressures above 500 or 300 MPa combined with heat would significantly inactivate these enzyme activities. Both color parameters and enzyme activities illustrated that though some enzymatic browning occurred with the pressurized products indicated by b* (yellowish) parameter, the magnitude of these browning was still milder than those thermally treated products indicated by-a* (greenness) and L (lightness) parameters, presumably as a consequence of the Maillard reaction. Moreover, the sensory scores were found in accordance with color parameters, firmness and capsaicin contents. © 2013 Copyright Taylor and Francis Group, LLC.